Customer satisfaction towards service quality of Melaka River Cruise / Farizan Nur ‘Izzati Mohd Khatib , Muhammad Wan Faiz Zulkefliy and Nurizzati Kamarulzaman - Mohd Khatib, Farizan Nur ‘Izzati; Kamarulzaman, Nurizzati; Zulkefliy, Muhammad Wan Faiz (Faculty of Hotel and Tourism Management, 2013)
First and foremost, state of Melaka is a historical city with domestic and international tourists that come over and enjoy the attractions available here. Apart from the main attraction of A’Famosa Porte De Santiago building, Melaka River Cruise (MRC) becomes the latest famous attraction in Melaka. MRC is a good experience for customer to get the new experience because they can see the real history of the Malacca state through the one of the historic river in the world. With the increasing number of tourist that come to experience the river cruise, the researchers intended to make a study on level of MRC service quality performance towards customer satisfaction. Using the cross- sectional study, the researchers carried out self-administered questionnaire to obtain results on customer satisfaction. The measurement of customer satisfaction used in this study was SERVQUAL by Parasuraman (1988). It is proven that among the all the dimensions of SERVQUAL, tangibility is the strongest predictor that affect customer satisfaction. Thus the researchers agreed to conclude that the management of MRC should emphasized on the tangibility of their product to further increase the customer satisfaction.